2016
DOI: 10.1177/1076029616654264
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Common CYP2C9 Polymorphisms and Their Impact on Warfarin Dose Requirement in Pakistani Population

Abstract: Polymorphisms in cytochrome P450 (CYP) 2C9 (CYP2C9) gene result in interindividual variability in warfarin dose requirement. There is a need for characterization of genotype frequency distribution in different populations for construction of customized dosing algorithms to enhance the efficacy and reduce the toxicity of warfarin therapy. This study was carried out in Pakistani population to evaluate the contribution of common CYP2C9 polymorphisms to warfarin therapy. A total of 550 stable patients taking warfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…Other studies on the North and the South Indian patients with mechanical heart valve showed that the patients carried the combination of variant alleles of CYP2C9*2, *3 and VKORC1-1639 and -1173 received lower dose of acenocoumarol treatment to reach INR from 2.5 to 3.0 [11,14]. Similar conclusions were proposed by Hungarian [12], Lebanese [13], Romanian [15], Pakistani [20]. A difference in our study to previous studies was that CYP2C9 polymorphism was not related to acenocoumarol dose in Vietnamese patients.…”
Section: Discussionsupporting
confidence: 72%
“…Other studies on the North and the South Indian patients with mechanical heart valve showed that the patients carried the combination of variant alleles of CYP2C9*2, *3 and VKORC1-1639 and -1173 received lower dose of acenocoumarol treatment to reach INR from 2.5 to 3.0 [11,14]. Similar conclusions were proposed by Hungarian [12], Lebanese [13], Romanian [15], Pakistani [20]. A difference in our study to previous studies was that CYP2C9 polymorphism was not related to acenocoumarol dose in Vietnamese patients.…”
Section: Discussionsupporting
confidence: 72%
“…To our knowledge, this is the first study to report frequencies of CYP2C9 gene polymorphisms in various ethnicities of the Pakistani population. Although there have been a few studies from Pakistan in which frequency of CYP2C9*2 and CYP2C9*3 were reported [29][30][31] , all of these studies involved patients with different diseases and, therefore, unable to capture the actual frequency of these polymorphisms in a general Pakistani population. The frequencies of CYP2C9*2 and CYP2C9*3 reported in these publications are 5.1% for CYP2C9*2, 15.4% for CYP2C9*3 in breast cancer patients 29 , 4.45% for CYP2C9*2, 22.8% for CYP2C9*3 in cardiovascular patients taking warfarin 31 and 12.1% for CYP2C9*2, 14.1% for CYP2C9*3 in heart valve replacement patients taking warfarin 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been a few studies from Pakistan in which frequency of CYP2C9*2 and CYP2C9*3 were reported 29 31 , all of these studies involved patients with different diseases and, therefore, unable to capture the actual frequency of these polymorphisms in a general Pakistani population. The frequencies of CYP2C9*2 and CYP2C9*3 reported in these publications are 5.1% for CYP2C9*2 , 15.4% for CYP2C9*3 in breast cancer patients 29 , 4.45% for CYP2C9*2 , 22.8% for CYP2C9*3 in cardiovascular patients taking warfarin 31 and 12.1% for CYP2C9*2 , 14.1% for CYP2C9*3 in heart valve replacement patients taking warfarin 30 . These frequencies vary significantly from one study to another and are also different from the ones we have reported for the healthy Pakistani population in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For CYP2C9*3, patients with homozygous variant genotype (*3/*3) warfarin dose was significantly lower than homozygous wild type (*1/*1), but the dose requirement of heterozygous variant genotypes was not significantly different. 13 That is why the overall variability caused by all 4 SNPs to the warfarin dose is small (3.8%). There is a wide range of dose variability explained by these genotypes, reported in other international studies.…”
Section: Discussionmentioning
confidence: 99%
“…4,[8][9][10][11][12] We have already studied CYP2C9 polymorphisms and their effect on warfarin dose in Pakistani population. 13 That study data were used to assess the overall influence of both CYP2C9 and VKORC1 polymorphisms on warfarin dose requirement in present study. To expedite the use of VKORC1 genotyping along with CYP2C9 genotypes routinely in anticoagulation practice, it is imperative to determine the allelic frequency in different populations.…”
Section: Introductionmentioning
confidence: 99%